Análise da situação da população rural do município de Jaboticabal (SP) - Ferreira, Bruna Jungles [UNESP]; Samara, Samir Issa [UNESP]; Fonseca, Maria Imaculada [UNESP]; Oliveira, João Ademir de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project was developed considering the joint teaching, research and extension, based on the need to analyze the consequences of growing changes faced by rural Brazil, which led to a reconfiguration of the productive structure and the living standards of the rural population of the municipality of Jaboticabal (SP). Given the above, this study aims to verify the socioeconomic situation of the rural population, raising existing data and investigating the reality of 23 properties located in the municipality. The results of this survey indicate that the municipality followed the Brazilian trend of crescent rural exodus, accompanied by the intense field mechanization and the focus on cultures that meet the growing demands in the region, as is the case of sugarcane. Results of this nature will allow the development of new research and subsidize the deployment of public policies more consistent with this new reality of the rural population.

O projeto foi desenvolvido considerando a articulação ensino, pesquisa e extensão, tendo como base a necessidade de analisar as consequências das crescentes modificações enfrentadas pelo meio rural brasileiro, que ocasionaram uma reconfiguração da estrutura produtiva, bem como dos padrões de vida da população rural do município de Jaboticabal (SP). Diante do exposto, este estudo objetiva verificar a situação socioeconômica da população rural, levantando dados já existentes, e apurando a realidade de 23 propriedades situadas no município. Os resultados deste levantamento apontam que o município seguiu a tendência brasileira de crescente êxodo rural, acompanhado pela mecanização intensa do campo e o foco em culturas que atendam às demandas crescentes na região, como é o caso da cana-de-açúcar. Resultados desta natureza possibilitarão o desenvolvimento de novas pesquisas e subsidiarão o desdobramento de políticas públicas mais condizentes com esta nova realidade da população rural.
Keywords: Rural characterization; Socioeconomic activity; Caracterização rural; Atividade socioeconômica